2021
DOI: 10.3390/nano11082046
|View full text |Cite
|
Sign up to set email alerts
|

Nanogold-Carried Graphene Oxide: Anti-Inflammation and Increased Differentiation Capacity of Mesenchymal Stem Cells

Abstract: Graphene-based nanocomposites such as graphene oxide (GO) and nanoparticle-decorated graphene with demonstrated excellent physicochemical properties have worthwhile applications in biomedicine and bioengineering such as tissue engineering. In this study, we fabricated gold nanoparticle-decorated GO (GO-Au) nanocomposites and characterized their physicochemical properties using UV-Vis absorption spectra, FTIR spectra, contact angle analyses, and free radical scavenging potential. Moreover, we investigated the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…Studies have shown that GO-modified composites promoted the polarization of macrophages toward the anti-inflammatory M2 phenotype, but the effect of GO on osteoclasts is rarely reported. In the study of Dou et al, GO was endocytosed by macrophages, and these activated macrophages subsequently enhanced the osteogenic function of BMSCs through the OSM signaling pathway. , The results of this experiment showed that the concentric microgrooves had clear inhibitory effects on the osteoclastogenic differentiation of macrophages, primarily by inhibiting the fusion of osteoclasts, while GO increased the hydrophilicity of the material, promoting macrophage migration into the microgrooves, and strengthening this inhibitory effect.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that GO-modified composites promoted the polarization of macrophages toward the anti-inflammatory M2 phenotype, but the effect of GO on osteoclasts is rarely reported. In the study of Dou et al, GO was endocytosed by macrophages, and these activated macrophages subsequently enhanced the osteogenic function of BMSCs through the OSM signaling pathway. , The results of this experiment showed that the concentric microgrooves had clear inhibitory effects on the osteoclastogenic differentiation of macrophages, primarily by inhibiting the fusion of osteoclasts, while GO increased the hydrophilicity of the material, promoting macrophage migration into the microgrooves, and strengthening this inhibitory effect.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo measurements showed that FN–AgNPs significantly inhibited the expression of pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6), promoted endothelialization for MSCs, and attenuated foreign body responses, demonstrating the potential vascular repair applications of FN–AgNPs [ 73 ]. Graphene oxide decorated with Au nanoparticles (Go–Au) was suggested to be a promising nanocarrier owing to its better biocompatibility and its ability to induce various differentiated cell types for MSCs such as neuron, endothelial cells, osteocytes, and adipocytes [ 74 ]. The synthetic polymer, polyethylene glycol (PEG), was combined with Au nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the production of a large amount of anti-inflammatory factors down-regulates the body’s resistance to external pathogenic microorganisms, so further modifications and designs of GO are needed. 147 , 148 Therefore, GO modification and design of GFNs for medical use should be considered to improve their clinical applications.…”
Section: Potential Risks Of Graphene Nanomaterialsmentioning
confidence: 99%